English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(1/x^2-3x) - (x-1)/(x^2-9)

2007-09-18 05:11:18 · 2 answers · asked by o d 1 in Science & Mathematics Mathematics

2 answers

1/(x^2-3x) - (x-1)/(x^2-9)
= 1/[(x)(x-3)] - (x-1)/[(x-3)(x+3)]
= [(x+3)-(x-1)(x)] / [(x)(x-3)(x+3)]
= [(x+3)-(x^2-x)] / [(x)(x-3)(x+3)]
= (2x+3-x^2) / [(x)(x-3)(x+3)]
= -(x^2-2x-3) / [(x)(x-3)(x+3)]
= -[(x-3)(x+1)] / [(x)(x-3)(x+3)]
= - (x+1) / [ (x)(x+3)]

2007-09-18 05:25:56 · answer #1 · answered by cllau74 4 · 0 0

I am assuming your expression is wrong. Instead I am going to simplify this

I/(x^2-3x) - (x-1)/(x^2-9)
= 1/(x(x-3) - (x-1)/(x+3)(x-3)

LCM for x(x-3) and (x+3)(x-3) = x(x-3)(x+3)

(x+3)/x(x+3)(x-3) - x(x-1)/x(x+3)(x-3)

(x+3 - x^2 +x)/x(x+3)(x-3)
-(x^2 -2x -3)/x(x+3)(x-3)
-(x-3)(x+1)/x(x+3)(x-3)
-(x+1)/x(x+3)

2007-09-18 12:27:20 · answer #2 · answered by norman 7 · 0 0

fedest.com, questions and answers